Análise histórica do fechamento das escolas localizadas no campo nos municípios que compõem o Núcleo Regional de Educação de Dois Vizinhos: o caso das escolas da Comunidade Canoas município de Cruzeiro do Iguaçu - 1980 - 2014 - Schmitz, Micheli Tassiana (2015)
This study investigated the process of closing schools located in rural areas of the municipalities that make up the Regional Center of Education of DoisVizinhos in the Southwest region of Paraná. From the data presented in the opinion 1011/10, DUDE / SEED / PR, which indicated that between the years 1990-1999 there was the closure of 3,948 schools in the field in Parana, the need for an investigation felt to understand the factors who contributed in reaching that amount. To this end it was held data collection by the Regional Center of Dois Vizinhos Education, Education Departments of Municipalities and Schools, about the number of schools and students, differentiating them from urban and rural, starting from the year 1980 until 2014. It was taken as a case study the closure of schools in Canoas community in the city of Cruzeiro do Iguaçu, the State School Field Canoas - Elementary School and the Municipal Rural School Santa Terezinha - Kindergarten and Elementary School. To understand the closure of these schools held interviews with members of Canoas community, staff, students and officials who held public office in the school closure period, it sought to documents, protocols and photos that could illustrate the historical construction and the process closings of these schools. The historic building naturalized the idea of the countryside as a delay of place where not made / make school education is required. The laws legitimized a dual education, where the children of the elite have comprehensive training and the children of the working class were formed to work. The modernization of agriculture allied with agribusiness has meant that small producers were expropriated the match, and their land stay with great owners. Thus it happened the emptying of the countryside and consequently the schools it decreased the number of students and have been and are being closed, without taking into account the socio-cultural context that these schools represent the impacts on communities and families. There are currently laws that ensure that schools be closed only after consultation with the community, or that schools be organized in alternative ways that meet students with quality, but these laws are not always implemented and many schools located in field find themselves threatened with fear of closing, or end up being closed.